Ultimate X-Men - Kirkman, Robert 1978-; Vaughan, Brian K. 1976- (Marvel Publishing, Inc., 2006)
In "Phoenix?" our heroes kick back for a night on the town with their significant others after the events of Magnetic North and their recent encounter with the master of magnetism. Meanwhile, Wolverine must face a dreaded foe from the past who comes back to haunt him with unbearable secrets that have been buried for years. Plus: Is Jean Grey really the cosmic entity called Phoenix? And if so, what can be done about it? And in Magical, meet the mysterious mutant called the Magician. He's a media darling, a vital part of the X-Men dynamic and the newest member of the team. Watch him live up to his name in ways you could never conceive. There is more -- much, much more about this new mutant than any suspect. Meanwhile, a tormented Jean Grey is having great difficulty dealing with the results of the Shi'ar testing. Elsewhere ... Dazzler stirs